Comparison of medication adherence in patients with type 2 diabetes mellitus: a pre and post study - M., Maheshwari; M. M., Mirudulaa; A., Sriram; P., Sakthivel; T., Saravanan; Rodrigues, Prudence A. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Type 2 diabetes mellitus refers to a group of heterogeneous disorders with the common elements of chronic hyperglycemia. Diabetes medications play a crucial role in lowering blood sugar levels. The study aims to compare medication adherence in patients with type 2 diabetes mellitus from urban and rural areas during pre and post visit. Methods: This pre and post-study was conducted from March to August 2022. A total of 104 participants were enrolled. Details have been obtained through data collection form. Medication adherence was measured using Hill-Bone medication adherence scale, and patient education was provided through leaflet. Results: The study included 54 females and 50 males. The correlation between medication adherence versus disease knowledge and drug knowledge was found out using Pearson’s correlation and the result is statistically significant. The medication adherence was found to be increased by 17.3% and 21.2% in rural and urban areas respectively. Inadequate follow-up and financial barriers were most accounted for medication non-adherence. Conclusions: The majority of type 2 diabetes patients have suboptimal treatment adherence which is associated with poor blood sugar control. We clinical pharmacists can tackle this problem of adherence through quality patient education.